Social Media as A Tool of Marketing (Trinity Journal of Management, IT & Media (TJMITM), 2021)
Abstract- Social media nowadays is among the ‘best possibilities available’ to an item to get in touch  with  potential  customers.  Community  social  networking  websites  are  the  method  to interact  socially.  Social  media  is  a  phenomenon  that  has  become  an  important  aspect  in marketing mix and revolutionizing the way companies interact with customers.These  new  media  win  the  believe  in  of  customers  by  linking  with  them  at  a  deeper  level. Community online marketing is the new mantra for several manufacturers since early a season ago. {ref. 7} Promoters are considering many different social media possibilities and beginning to  apply  new  social  projects at  a  higher  rate  than  ever  before.  Community  online  marketing and the companies that utilize it have become more sophisticated. One cannot afford to have no existence on the social programs if the competitor is creating waves with its solutions and items.  The  blast  of  social  media  trend  is  as  amazing  as  that  and  the  speed  at  which  it  is improving is frustrating.The findings presented in this study conclude that even though social media is more effective than  some  of  the  traditional  advertising  channels,  it  cannot  be  implemented  in  isolation without augmenting it with other forms of traditional advertising channels.
Keywords: Social Media; Brand Awareness; Brand Management; Marketing Mix; Traditional Advertising channels